2005
DOI: 10.2113/4.1.41
|View full text |Cite
|
Sign up to set email alerts
|

Spatial Variability and Transport of Nitrate in a Deep Alluvial Vadose Zone

Abstract: Little empirical evidence exists about the spatial distribution of NO3–N in deep vadose zones and about the associated fate and transport of NO3–N between the root zone and the water table. We investigated NO3–N occurrence in a deep alluvial vadose zone and its relation to geologic site characteristics, hydraulic properties, and fertilizer application rates via an intensive three‐dimensional core‐sampling campaign beneath an irrigated orchard in semiarid Fresno County, California. Statistical and geostatistica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

12
71
0

Year Published

2005
2005
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 62 publications
(83 citation statements)
references
References 62 publications
(81 reference statements)
12
71
0
Order By: Relevance
“…More than half of those occurred in the subplot with the highest nitrogen application. Mean nitrate-nitrogen concentrations (not including nondetects) in the control, standard and high subplot vadose zone were estimated to be 5.2, 3.3 and 7.4 mg/L, respectively (Onsoy et al 2005). The nitrate-nitrogen coefficient of variation (CV) ranged from 1.6 to 2.4 within each subplot.…”
Section: Nitrogen Distributionmentioning
confidence: 97%
See 1 more Smart Citation
“…More than half of those occurred in the subplot with the highest nitrogen application. Mean nitrate-nitrogen concentrations (not including nondetects) in the control, standard and high subplot vadose zone were estimated to be 5.2, 3.3 and 7.4 mg/L, respectively (Onsoy et al 2005). The nitrate-nitrogen coefficient of variation (CV) ranged from 1.6 to 2.4 within each subplot.…”
Section: Nitrogen Distributionmentioning
confidence: 97%
“…Hydraulic properties of the unsaturated zone, such as the hydraulic conper year (Onsoy et al 2005). Assuming uniform flow conditions throughout the deep vadose zone at an average soil moisture content of 25%, the travel time through the deep vadose zone was projected to be 3.2 (± 0.5) years.…”
Section: Hydraulic Properties Variabilitymentioning
confidence: 99%
“…Knowledge of nitrate's fate and transport below the root zone is restricted due to issues such as soil spatial variability and long travel times in the deep vadose zone (Onsoy et al, 2005). Moreover, estimates of cumulative nitrate fluxes in the unsaturated zone have shown significant differences in the timing and magnitude of fluxes derived from different land uses (Green et al, 2008;Turkeltaub et al, 2014Turkeltaub et al, , 2015b.…”
Section: Introductionmentioning
confidence: 99%
“…Many studies conducted in areas under different land uses e.g., bare land (Ronen et al, 2000;Kurtzman et al, 2011), fertilized fields (Onsoy et al, 2005), agriculture areas irrigated with fresh water (Stonestrom et al, 2003) and with treated sewage effluents (TSE; Kurtzman et al, 2011), have shown large differences in the concentration of non-conservative and even conservative components in VZ interstitial water. For example, in California variability in nitrate concentration of up to about 90 mg/L was detected at lateral distances of 2 m in a 15 m deep alluvial VZ subjected to flood irrigation (Onsoy et al, 2005).…”
Section: Introductionmentioning
confidence: 99%